Burnout Prevalence in Special Education Teachers, and the Positive Role of ICTs - Stathopoulou, Agathi; Spinou, Despina; Driga , Anna-Maria (International Journal of Online and Biomedical Engineering (iJOE), 2023)
The aim of this study was to investigate special education teacher`s level of burnout. In particular, it sought to examine the role their personal characteristics play in the occurrence of the syndrome. A quantitative research design was used to describe the association between the variables The data was collected using the Maslach Burnout Inventory for Education (M.B.I.-E.S.) consisted of three dimensions: Emotional exhaustion, Depersonalization, and Personal accomplishment. The sample consisted of 202 Special Education (S.E) teachers who completed the M.B.I.-E.S. The results of this research showed that: a) the sample experiences burnout and special attention is required for the scale of emotional exhaustion b) age, school settings , specialty, and the total previous service with or without students with special educational needs (S.E.N.) were significantly correlated and affected burnout dimensions